THE EFFECT OF EXTRACTS OF CURCUMA ZEDOARIA ON THE EXPRESSION OF THE PROINFLAMMATORY CYTOKINE TNF-α - Mozartha, Martha; Hudiyati, Maya; Anastasia, Danica (International Journal of Islamic and Complementary Medicine, 2022)
Curcuma zedoaria is known to have antibacterial and antifungal activity, and have the potential to be used as an irrigation solution in endodontic treatment. Endodontic irrigant that is going to be used clinically has to go through a series of research, to ensure effectiveness and safety without adverse side effects. The purpose of this study was to determine the effect of extracts of C. zedoaria with concentrations of 5%, 10%, and 20% as endodontic irrigation on the expression of the proinflammatory cytokine TNF-α on Wistar rat. This experimental study used extracts of C.zedoaria with concentrations of 5%, 10%, 20%, as tested groups, 5.25% sodium hypochlorite as the positive control, and saline solution as a negative control group. Thirty male adult Wistar rats (Rattus novergicus) with an average weight of 150-200 g were included in this study. The dermis of each rat was marked with a circle and 0.1 ml of each irrigant was injected subcutaneously by using a syringe. The evaluation was made 14 days after injection. The expression of cytokine TNF-α was assessed with the IHC method. The percentage of TNF-α expression was evaluated and analyzed by using One-way Anova followed by Tukey Post Hoc test. The results of this study revealed that the highest percentage of TNF-α expression is positive control group (5.25% NaOCl). Furthermore, the higher the concentration of C. zedoaria extract, the greater the percentage of TNF-α expression. One-way Anova results showed that there was a significant difference between groups (p ≤ 0.05). From the results of the Tukey test, it was found there was a significant difference between groups except between the negative control group and the 5% extract group. It can be concluded that C. zedoaria extract 10 and 20% can increase TNF-α expression, but its ability is lower than sodium hypochlorite.